Development of an AHP–TOPSIS Decision Support System for Clamp Plunger Vendor Selection - Sulkhan Sulkhan; Siti Nana Alfiyah (Mandalika Institute, 2026)
The selection of vendors for critical machine components is essential for maintaining machine reliability, minimizing maintenance costs, and ensuring continuous production in the non-dairy creamer industry. However, previous AHP–TOPSIS studies have predominantly focused on conventional procurement criteria, with limited attention to the operational consequences of selecting critical spare-part vendors, particularly their effects on machine reliability, gasket service life, maintenance downtime, and lifecycle maintenance costs. This study addresses this gap by developing an integrated Decision Support System (DSS) based on the Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) for clamp plunger vendor selection. Five evaluation criteria—clamp price, lead time, product quality, impact on gasket service life, and vendor service and repair support—were applied to evaluate three vendor alternatives (Wirasakti, Prosper, and Asahan) using expert judgments and operational data. The AHP analysis identified product quality as the most influential criterion (49.35%), followed by impact on gasket service life (24.32%), vendor service and repair support (12.22%), clamp price (9.44%), and lead time (4.66%), with a consistency ratio of 0.042. The TOPSIS results ranked Wirasakti as the best vendor (0.871), followed by Prosper (0.813) and Asahan (0.187). The novelty of this study lies in integrating vendor evaluation with machine reliability and maintenance performance indicators, extending vendor selection beyond conventional procurement considerations. The proposed DSS provides a systematic and objective framework that supports reliability-oriented procurement decisions, helping manufacturers reduce maintenance downtime, improve component lifecycle performance, and enhance sustainable production efficiency.